En pilotstudie av unghästars användning av ligghall i grupphållningssystem - Brosäter, Carin; Peterhoff, Gabriella (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2013)
Today, individual indoor stalls and individual outdoor paddocks are the most common way to house horses in Sweden. The way that we manage, house and feed the horses are not optimal for the species natural basic behavioural needs. However, the awareness of this grows in the context of research and the emergence of alternative housing systems. One of the alternatives to the traditional format in individual boxes is called group housing. Group housing systems allow horses to live in herds and they can choose how they want to distribute the hours of the day between movement, resting and foraging.